Mineral nutritional status of blast infected rice plant and allied soil (Journal of the Bangladesh Agricultural University, 2020)
In recent years, the outbreak of rice blast is causing severe damage to rice production in Bangladesh. A research work was carried out at the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh to determine the concentration of different plant nutrients in rice blast infected plant and allied prior to harvest soil samples and also to recognize the role of plant nutrients in rice blast disease outbreak through comparing them with different reference values. A total of 20 infected mature rice plants and allied prior to harvest soil samples were randomly collected from Gazipur sadar upazila and Mymensingh sadar upazila of Bangladesh in April 2018. Comparison with the reference value suggested that Si and Ca concentrations in all the infected rice plant samples, and S and Mg concentrations of 70% samples were within the low level and K concentration in all the infected samples were found at very low level. The concentrations of P in all the plant samples were within the high level and the concentration of B was greater than the high level as compared to the reference values. The available concentrations of P, K and Si in soil samples was low but B concentration was high and the concentration of S was adequate. On the other hand, Ca and Zn concentrations of 70% and 60% samples were within the high category, respectively. The analyzed result revealed that available Ca concentration in soil was adequate but the plant could not uptake enough Ca and it found at a low level in the infected plant. Both soil and plant samples contained a high level of B which might lead to toxicity and increase the susceptibility of rice plants for blast infection. Both the collected plants and allied prior to harvest soil samples contained low amount of Si which might be the reason for the occurrence of blast disease in rice. Plant nutrients like Ca, B and Si should be considered in outlining rice blast disease management plan due to their vital role.J Bangladesh Agril Univ 18(2): 395–404, 2020https://doi.org/10.5455/JBAU.81279